Smart People KTM Sungai Rambutan-Parit Kabupaten Ogan Ilir: Studi Problematika Penduduk Transmigran - Saputra, Ardi; Sri Andriani, Dian; Helmi, Henny; Septiani, Yin Yin (Universitas Tribhuwana Tunggadewi, 2024)
Community development is an effort to improve the quality of social life in society. Quality improvement is also an inseparable part of regional development. This research aims to determine the potential of the transmigrant population in the context of smart people in the Mandiri Integrated City area of Sungai Rambutan and Parit. This research uses mixed methods with a research focus on digital education and community creativity. The research results show that the transmigrant community does not meet the criteria for being smart people. This is in accordance with survey data that the digital education variable with the digital mastery indicator of 78% is not met and the openness indicator of 66% is not met. Meanwhile, for the flexible indicator skills variable, 70% were not met, 76% were satisfied with the desire to develop, 82% were met for ethnic and social plurality, and 77% were fulfilled for participation in life together. The results of the research can be concluded that there are still problems with KTM Sungai Rambutan-Parit being able to become a smart people area.Pembangunan masyarakat merupakan salah satu upaya peningkatan kualitas hidup sosial di masyarakat. Peningkatan kualitas juga merupakan bagian yang tidak terpisahkan dari pembangunan wilayah. Penelitian ini bertujuan untuk mengetahui potensi penduduk transmigran dalam konteks smart people di kawasan Kota Terpadu Mandiri Sungai Rambutan dan Parit. Penelitian ini menggunakan metode campuran dengan fokus penelitian pada edukasi digital dan kreatifitas masyarakat. Hasil penelitian menunjukan bahwa masyarakat transmigran belum memenuhi kriteria sebagai smart people. Hal ini sesuai dari data survey bahwa variabel edukasi digital dengan indikator penguasaan digital 78% tidak terpenuhi dan indicator keterbukaan 66% tidak terpenuhi. Sedangkan pada variabel keterampilan indikator fleksibel 70% tidak terpenuhi, keinginan untuk berkembang 76%, pluralitas etnik dan sosial 82% terpenuhi, dan partisipasi dalam kehidupan bersama 77% terpenuhi. Hasil penelitian dapat disimpulkan bahwa masih terdapat permasalahan pada KTM Sungai Rambutan-Parit untuk dapat menjadi kawasan yang smart people